Two new xanthones from Artocarpus obtusus - Hashim, Najihah; Rahmani, Mawardi; Sukari, Mohd A.; Ali, Abdul M.; Mohamed Alitheen, Noorjahan Banu; Go, Rosea; M. Ismail, Hazar B. (Taylor&Francis, 2010)
Two new xanthones, pyranocycloartobiloxanthone A (1) and dihydroartoindonesianin C (2), were isolated from the stem bark of Artocarpus obtusus Jarrett by chromatographic separation. Their structures were determined by using spectroscopic methods and comparison with known related compounds. Pyranocycloartobiloxanthone A (1) showed strong free radical scavenging activity by using DPPH assay as well as cytotoxicity towards K562, HL-60, and MCF7 cell lines.